Intranasal lidocaine and midazolam for procedural sedation in children. - Chiaretti, Antonio; Barone, Giuseppe; Rigante, Donato; Ruggiero, Antonio; Pierri, Filomena; Barbi, Egidio; Barone, Giovanni; Riccardi, Riccardo (Arch Dis Child, 2011)
OBJECTIVE: To evaluate the safety and efficacy of a sedation protocol based on intranasal lidocaine spray and midazolam (INM) in children who are anxious and uncooperative when undergoing minor painful or diagnostic procedures, such as peripheral line insertion, venipuncture, intramuscular injection, echocardiogram, CT scan, audiometry testing and dental examination and extractions. PATIENTS AND DESIGN: 46 children, aged 5-50 months, received INM (0.5 mg/kg) via a mucosal atomiser device. To avoid any nasal discomfort a puff of lidocaine spray (10 mg/puff) was administered before INM. The child's degree of sedation was scored using a modified Ramsay sedation scale. A questionnaire was designed to evaluate the parents' and doctors' opinions on the efficacy of the sedation. Statistical analysis was used to compare sedation times with children's age and weight. RESULTS: The degree of sedation achieved by INM enabled all procedures to be completed without additional drugs. Premedication with lidocaine spray prevented any nasal discomfort related to the INM. The mean duration of sedation was 23.1 min. The depth of sedation was 1 on the modified Ramsay scale. The questionnaire revealed high levels of satisfaction by both doctors and parents. Sedation start and end times were significantly correlated with age only. No side effects were recorded in the cohort of children studied. CONCLUSIONS: This study has shown that the combined use of lidocaine spray and atomised INM appears to be a safe and effective method to achieve short-term sedation in children to facilitate medical care and procedures.
Keywords: Administration, Intranasal; Anesthetics, Local; Anxiety; Child, Preschool; Conscious Sedation; Diagnostic Techniques and Procedures; Female; Humans; Hypnotics and Sedatives; Infant; Lidocaine; Male; Midazolam; Minimally Invasive Surgical Procedures; Nebulizers and Vaporizers; Nose Diseases; Prospective Studies